The second continuous Jacobi transform. (1985) - Deeba, E. Y.; Koh, E. L.
Abstract : This paper continues the work started in [1]; a second continuous Jacobi transform is defined for suitable functionsf ( x ) . Properties of the transform are studied. In particular, the first continuous Jacobi transform in [1] and the second continuous Jacobi transform are shown to be inverse to each other. The paper concludes with an extension of Campbell's sampling theorem [2].